THE INFLUENCE OF NAHWU AND SHORROF MASTERY ON THE ABILITY OF THE STUDENTS OF KSK FATHIMATUZZAHRO' - Sumiati, Sumiati; Wijaya, Muallim (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the effect of students' mastery of nahwu and shorrof material on mastery of insya' writing skills. The method used in this research is to use a quantitative method that uses the entire population to be sampled at the Fathimatuzzahro Special Study Group Institute (KSK), because the population is very small. Collecting data in this study using tests, observation and documentation. The analysis technique to determine the validity of the results uses product moment correlation and determines the influence between variable X and variable Y using simple linear regression analysis with the help of SPSS. The results showed that the average score for mastery of nahwu and shorrof material was 78.42, the median was 75 mode 75 and based on the data generated through the test. The results of the study showed that the average score for mastery of writing skills insya' was 82.5, the median was 82.5, the mode was 70 and based on the data generated through the test. And there is an influence of mastery of nahwu and shorrof learning on students' writing skills, insya' based on the significant value generated through hypothesis testing, namely 0.000 <0.05 and based on a significant test on the coefficient table of 0.000 <0.05 meaning that there is a significant influence between mastery of nahwu mastery and shorof on the ability to write essays insya' students (KSK) fathimatuzzahro.